2009
DOI: 10.1007/s10562-009-9880-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Thiophene on Inorganic MoS2 Fullerene-Like Nanoparticles

Abstract: The catalytic activity of a rather new nanomaterial, IF-MoS 2 (inorganic fullerene-like nanoparticles), towards hydrodesulfurization (HDS) activity has been characterized at ultra-high vacuum conditions. Thiophene TDS as well as quasi steady-state kinetics experiments have been conducted. The IF-MoS 2 nanoparticles were supported on sapphire and silica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…It is important to note that care must be taken when analyzing the data reported by these authors. Indeed, in a subsequent work [10], the same group found that the data obtained during the study of the adsorption of methanol on nanotubes was affected by rather subtle solvent (impurity) effects. In particular, they recommended that very clean nanotubes should be used when studying the adsorption of polar molecules, even though for apolar molecules the requirements are less severe.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that care must be taken when analyzing the data reported by these authors. Indeed, in a subsequent work [10], the same group found that the data obtained during the study of the adsorption of methanol on nanotubes was affected by rather subtle solvent (impurity) effects. In particular, they recommended that very clean nanotubes should be used when studying the adsorption of polar molecules, even though for apolar molecules the requirements are less severe.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the graphenelike two-dimensional (2D) transition metal dichalcogenides (TMDs) are promising sorbents for removal of contaminants due to their unique layered structures and large surface area [19][20][21]. For example, Chao et al [22] used ultra-thin MoS 2 nanosheets to remove toxic organics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various techniques have been applied to remove organic pollutant from wastewater including chemical oxidation method, biodegration [5], photocatalysis and adsorption [6][7][8]. Among them, adsorption has been considered as a promising and efficient method to remove organic pollutant from aqueous solutions due to low cost, convenient operation, flexibility, small amounts of harmful substances and simple design [8][9][10][11]. It is a universally acknowledged truth that adsorption efficiency relies on the development of high-performance adsorbent, and adsorption properties are significantly affected by the structures and chemical composition of adsorbents.…”
Section: Introductionmentioning
confidence: 99%